Administrative justice: problems of theoretical and methodological modeling (Journal of actual problems of jurisprudence, 2018)
Despite all the attempts perceived within the confines of ongoing administrative and legal reforms, the administrative justice of Kazakhstan has not yet been fully formed and is at the stage of its formation. The processes of further development of administrative justice call for the need for a more detailed elaboration of this problem with the application of advanced international experience in this area of public law activity of the state. In order to fill the gaps that have formed, at all stages of state reform, in Kazakhstan issues were sharply raised whose solution was aimed at improving administrative legislation and, in general, administrative and legal relations. Another basic idea of the ongoing reforms was the idea of the formation of administrative justice and administrative proceedings, which, according to its purpose, was to become a full-fledged form of administration of justice, along with criminal and civil proceedings. The administrative justice within the Kazakh legal system should be considered only within the confines of the theory of administrative and legal relations, that is, administrative (public) disputes must be considered within the confines of the administrative justice that is strictly included in the field of activity, administrative courts in the procedure of administrative proceedings. Key words: administrative justice, administrative law, administrative legal proceedings, judicial control, judicial protection, rights and freedoms, justice, public-law disputes, administrative and legal reforms.